Islamic Education System of Minangkabau Society: Analysis Review of 17th-18th Century - Syamsudin, Syamsudin; Amin, Muhammad; Saputra, Dodi; Rambe, Anggi Afrima; Iskandar, M. Yakub (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
Surau as the oldest Islamic educational institution in Minangkabau can produce scholars who are hard to find anymore today. This study aims to analyze the objectives of Surau education, the materials studied, and the methods used in Surau education in Minangkabau in the 17th-18th century. This study uses a library research method with a descriptive approach. The primary data source in this study is the book: History of Islamic Education in Minangkabau in the 17th-18th Century. Surau: Traditional Islamic Education in Transition and Modernization, Syekh Burhanuddin and the Islamization of Minangkabau (syarak mandaki adat manurun). While the secondary data are books and journals related to the discussion. The technique used to analyze the data in this study is content analysis or document analysis, a systematic review of document records as data sources. The results of the analysis show that: 1) Surau education emphasizes more on upholding Islam amid life as the main source of morals or noble character which is the key to success in life in society, 2) The materials taught at Surau Syekh Burhanuddin include teaching the Qur'an, fiqh (Islamic law), morals, faith, neurology, nahu science, interpretation, hadith, tasawwuf science (tarekat), arts and other sciences, 3) The methods used in Surau in Minangkabau in the 17th-18th centuries were using the sorogan method, halaqah wetonan, memorization and training. The results of this study can be used as initial data for subsequent research in examining this problem in different contexts and issues.